ANALYSIS OF TRANSLATION OF THE NON-FINITE FORM OF THE ENGLISH VERB - Izzatulloyeva Maftuna (TADQIQOTLAR, 2025)
Annotation: This article analyzes the translation of non-finite forms of English verbs into several languages, emphasizing their structural and functional characteristics. The research examines the translation of infinitives, gerunds, and participles into target languages, assessing the difficulties translators encounter in maintaining semantic, grammatical, and stylistic subtleties. The essay elucidates ways for addressing disparities in language systems and underscores the significance of context in attaining precise and natural translations through examples and comparative study. The results enhance comprehension of verb forms in translation studies and offer pragmatic suggestions for translators.